Pengaruh Content Creation, Content Sharing, Connecting dan Community Building terhadap Keputusan Pembelian Konsumen pada 3D Stable Equestrian - Palda, Anya Irisha; Iisnawati, Iisnawati; Yunita, Dessy (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This research aims to determine the influence of content creation, content sharing, connecting and community building on consumer purchasing decisions on 3D Stable Equestrian. The research method used is a quantitative method. The data used in this research is primary data. The sampling technique uses purposive sampling technique. The sample studied in this research was 100 respondents who were 3D Stable Equestrian consumers. Based on the t test carried out, it can be concluded that partially content creation, content sharing, connecting and community building have a significant effect on consumer purchasing decisions at 3D Stable Equestrian. Content creation, content sharing, connecting and community building simultaneously have a significant influence on consumer purchasing decisions at 3D Stable Equestrian. The coefficient of determination of the content creation, content sharing, connecting and communitu building variables on the purchasing decision variable is 46,3%